Homeodomain interacting protein kinase (HPK‐1) is required in the soma for robust germline proliferation in C. elegans. Issue 11 (2nd September 2013) - Berber, Slavica; Llamosas, Estelle; Thaivalappil, Priya; Boag, Peter R.; Crossley, Merlin; Nicholas, Hannah R.
<x xml:space="preserve">Abstract</x> Background: Tightly regulated pathways maintain the balance between proliferation and differentiation within stem cell populations. In Caenorhabditis elegans, the germline is the only tissue that is maintained by stem‐like cells into adulthood. In the current study, we investigated the role played by a member of the Homeodomain interacting protein kinase (HIPK) family of serine/threonine kinases, HPK‐1, in the development and maintenance of the C. elegans germline. Results: We report that HPK‐1 is required for promotion of germline proliferation during development and into adulthood. Additionally, we show that HPK‐1 is required in the soma for regulation of germline proliferation. We also show that HPK‐1 is a predominantly nuclear protein expressed in several somatic tissues including germline‐interacting somatic cells. Conclusions: Our observations are consistent with a conserved role for HIPKs in the control of cellular proliferation and identify a new context for such control in germ cell proliferation. Developmental Dynamics 242:1250–1261, 2013. © 2013 Wiley Periodicals, Inc.